2018
DOI: 10.29312/remexca.v3i4.1423
|View full text |Cite
|
Sign up to set email alerts
|

Evolución nutrimental foliar en tres cultivares de mango en Nayarit, México

Abstract: Para desarrollar programas de fertilización de sitio específico en el cultivo del mango, es necesario disponer de información propia para cada región productora. El objetivo de este trabajo fue determinar la evolución de macro- y micronutrimentos a través de la vida de las hojas de los f lujos vegetativos de los cvs. Ataulfo, Kent y Tommy Atkins. Los huertos se localizaron en cuatro municipios del estado de Nayarit con clima cálido subhúmedo, en alturas de 11 a 601 m y temperatura … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
4
0
3
Order By: Relevance
“…During this period presented the development of stolons, flowering and fruit development, representing a very strong demand for minerals. Pineda-Pineda et al (2008) in red raspberry and Molina et al (1993) in strawberry 'Chandler 'observed the increased extraction of nutrients during the production of foliage and fruit; during flowering and fruit development in mango (Castro-López et al, 2012.). The extraction of nutrients from the DDT 184 is due to the strong demand of a plant by the development of stolons, flowers and fruits, which led to high accumulation of total dry matter (Table 1), which coincides with the results obtained by Molina et al (1993), who indicate that the higher dry matter accumulation increased absorption of nutrients occurs.…”
Section: Dynamics Of Nutrient Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…During this period presented the development of stolons, flowering and fruit development, representing a very strong demand for minerals. Pineda-Pineda et al (2008) in red raspberry and Molina et al (1993) in strawberry 'Chandler 'observed the increased extraction of nutrients during the production of foliage and fruit; during flowering and fruit development in mango (Castro-López et al, 2012.). The extraction of nutrients from the DDT 184 is due to the strong demand of a plant by the development of stolons, flowers and fruits, which led to high accumulation of total dry matter (Table 1), which coincides with the results obtained by Molina et al (1993), who indicate that the higher dry matter accumulation increased absorption of nutrients occurs.…”
Section: Dynamics Of Nutrient Removalmentioning
confidence: 99%
“…Pineda -Pineda et al (2008) en frambueso rojo y Molina et al (1993) en fresa 'Chandler', observaron la mayor extracción de nutrimentos durante la producción de follaje y de frutos; durante la floración y desarrollo de fruto en mango (Castro-López et al, 2012). La extracción de los nutrimentos a partir de los 184 ddt, se debe a la fuerte demanda que tiene la planta por el desarrollo de los estolones, las flores y frutos, lo que conllevó a la máxima acumulación de materia seca total (Cuadro 1), lo cual coincide con los resultados obtenidos por Molina et al (1993), quienes indican que a mayor acumulación de materia seca se presenta mayor absorción de nutrimentos.…”
Section: Dinámica De La Extracción Nutrimentalunclassified
“…In the summer of 2010, explorations were made Nayarit and marked with GPS (GPS, Garmin E-Trex H, Taiwan) nanche trees for fruit collection in the towns of the municipalities listed in Table 1. The climate in the coastal area where the collection of fruit were made is warm sub humid with summer rains (1 089 to 1 300 mm from July to October); annual average temperature of 21.7 to 22.7 °C (Castro-López et al, 2012).…”
Section: Genotypes Exploration and Collection Of Nanche Of Commercialmentioning
confidence: 99%
“…En el verano de 2010, se hicieron exploraciones en Nayarit y se ubicaron con un geoposicionador (GPS, Garmin ® , E-trex H, Taiwán) árboles de nanche para la recolección de frutos en las localidades de los municipios indicados en el Cuadro 1. El clima predominante en la zona costera donde se llevaron a cabo las colectas de frutos es cálido subhúmedo, con lluvias en verano (1 089 a 1 300 mm de julio a octubre); temperatura media anual de 21.7 a 22.7 °C (Castro-López et al, 2012).…”
Section: Materiales Y Métodos Exploración De Genotipos Y Colecta De Funclassified
“…Leaf mineral concentrations are affected by several factors. In Nayarit, Mexico, the evolution of foliar macro and micronutrients varied among Ataulfo, Kent and Tommy Atkins cultivars, and it was influenced by leaf age, vegetative flush, and tree phenology (Castro-López et al, 2012). In an organic mango orchard in Veracruz, Mexico, leaf nutrient concentrations were also affected by cultivar and tree phenology.…”
Section: Introductionmentioning
confidence: 99%